2018
DOI: 10.1177/2399654418788675
|View full text |Cite
|
Sign up to set email alerts
|

Contesting deep sea oil: Politicisation–depoliticisation–repoliticisation

Abstract: Between 2010 and 2017, the New Zealand Government undertook a range of subtle yet disturbing tactics to create a legislative environment that enabled deep sea oil exploration. This included forms of public endorsement, policy documents and legislative change that prioritised further oil development in the country to create a certain common-sense around increased fossil fuel extraction. In response, a range of communities and autonomous Oil Free groups have emerged to contest both the legislative changes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Politics is not about opposition between groups with different interests, it is a conflict between the logic of who and what is counted as a part of the community. Bond, Diprose and Thomas (2019) suggest that the very possibility of dissensus emerges from an assertion of equality, and so by focusing on articulations of equality in particular contexts, we can better understand how more democratic moments of dissensus can occur.…”
Section: Jacques Rancière Democratic Accountability and Dissensusmentioning
confidence: 99%
“…Politics is not about opposition between groups with different interests, it is a conflict between the logic of who and what is counted as a part of the community. Bond, Diprose and Thomas (2019) suggest that the very possibility of dissensus emerges from an assertion of equality, and so by focusing on articulations of equality in particular contexts, we can better understand how more democratic moments of dissensus can occur.…”
Section: Jacques Rancière Democratic Accountability and Dissensusmentioning
confidence: 99%
“…In order to allow for change to become possible within existing (or reformed) institutions, the spaces of that debate have to be widened. What we found in the Denniston case, and in other research (see Bond et al, 2018), is that antagonism plants seeds and ideas, which in turn might gradually expand the spaces of debate, such that what was once noise in Rancière’s terms becomes the fringes of legitimised arguments and begins to be heard. Then change becomes possible.…”
mentioning
confidence: 49%
“…We think it is fair to say that as neoliberalism has taken hold since the 1980s across the developed world and beyond, the appetite for and legitimacy given to participatory processes have lessened (Brown, 2015). This is a discursive and performative shift that has shaped how institutions and people engage with democratic processes (and here we do not mean just the institutions of representative democracy – see Bond et al, 2018; Purcell, 2009; Wilson and Swyngedouw, 2014). For example, Wendy Brown (2015) (perhaps provocatively) writes that… neoliberalism assaults the principles, practices, cultures, subjects and institutions of democracy understood as rule by the people.…”
mentioning
confidence: 99%
“…Regulative and legislative changes were made, and transnational oil and gas corporations were encouraged to invest. As noted above, elsewhere we have documented the ways in which government actions, the media, and climate justice activists have contested and debated oil and gas exploration in the EEZ (see Bond et al, 2019;Diprose et al, 2017). Our work is theorised in relation to both a broad ethos of democracy (requiring a vibrant contestatory sphere) and the kind of post-politicising processes, tactics, and discourses that are entangled with contemporary forms of neoliberal global capitalism.…”
Section: Politicsmentioning
confidence: 94%
“…While the context of this study is obviously unique to Aotearoa New Zealand, political theorists have observed that in many first-world neoliberal contexts, democracy has been eroded and the spaces for dissent have narrowed (e.g., Brown, 2015; Crouch, 2004;Mouffe, 2013). We also highlighted the ways in which pragmatic realism is occasionally interrupted by various forms of dissent (Bond et al, 2019). In relation to oil and gas exploration in the EEZ, that dissent was primarily by climate justice activists, who had formed small, networked, but autonomous groups around the countryoften taking the title of "Oil Free" followed by the name of the city.…”
Section: Politicsmentioning
confidence: 99%